2020
DOI: 10.3390/ma13020466
|View full text |Cite
|
Sign up to set email alerts
|

Parameters Influencing the Outcome of Additive Manufacturing of Tiny Medical Devices Based on PEEK

Abstract: In this review, we discuss the parameters of fused deposition modeling (FDM) technology used in finished parts made from polyether ether ketone (PEEK) and also the possibility of printing small PEEK parts. The published articles reporting on 3D printed PEEK implants were obtained using PubMed and search engines such as Google Scholar including references cited therein. The results indicate that although many have been experiments conducted on PEEK 3D printing, the consensus on a suitable printing parameter com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 31 publications
1
53
0
Order By: Relevance
“…It is worth noting that the electro-spinning approach has gained considerable attention from biomedical experts all around the world for manufacturing various polymers, particularly CS-based polymer scaffolds loaded with drugs for biomedical and wound dressing purposes [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ]. Application of CS-based biopolymers through 3D [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ] printing for biomedical purposes especially as bio-ink in an effort to fabricate complex tissues will probably be an upcoming pattern of 3D printing materials progression. However, CS and CS/Col designed bio-printed skin tissue has not already obtained the FDA approval, taking into account the similarity of constructed materials with some other permitted materials.…”
Section: Benefits Limitations and Future Prospectsmentioning
confidence: 99%
“…It is worth noting that the electro-spinning approach has gained considerable attention from biomedical experts all around the world for manufacturing various polymers, particularly CS-based polymer scaffolds loaded with drugs for biomedical and wound dressing purposes [ 172 , 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ]. Application of CS-based biopolymers through 3D [ 181 , 182 , 183 , 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 , 195 , 196 ] printing for biomedical purposes especially as bio-ink in an effort to fabricate complex tissues will probably be an upcoming pattern of 3D printing materials progression. However, CS and CS/Col designed bio-printed skin tissue has not already obtained the FDA approval, taking into account the similarity of constructed materials with some other permitted materials.…”
Section: Benefits Limitations and Future Prospectsmentioning
confidence: 99%
“…In recent years, a huge amount of research effort has been devoted to studying polyetheretherketone(PEEK) and its application in the biomedical field [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Three-dimensional printing of PEEK is carried out via fused deposition modeling (FDM) or fused filament fabrication (FFF) and associated with significant challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to SLS technology, material extrusion-based fused filament fabrication (FFF) technology is already integrated into the hospitals for the fabrication of anatomical biomodels, customized surgical tools, and prosthetic aids [ 9 ]. Besides, recent technological advancements in FFF 3D printers have made it possible to process high-temperature PEEK thermoplastic biomaterial [ 13 ]. In the FFF process, a filament is continuously extruded from a heated nozzle in a viscous state and deposited in a layer-by-layer manner to form the desired shape of an object.…”
Section: Introductionmentioning
confidence: 99%
“…This technology currently contributes to a new point-of-care (POC) workflow, implementing how PEEK medical implants need to be designed, developed, and manufactured for low-volume and on-demand production. Previous studies have demonstrated the feasibility of using FFF for medical PEEK printing [ 13 , 17 ]. As this technology is recognized as a prospective tool in the medical sector for in-hospital manufacturing of customized PEEK implants, the extent to which it affects the geometry and manufacturing quality remain under investigated.…”
Section: Introductionmentioning
confidence: 99%